"A friend or A Foe" determining factors contributed to the use of ChatGPT among university students - Yifan, Wang; Mengmeng, Yang; Omar, Muhd Khaizer (Human Resource Management Academic Research Society (HRMAS), 2023)
ChatGPT has become one of the most heated discussion in academia. With the continuous development of educational technology, ChatGPT is a kind of natural language processing technology which is widely applied in language models, dialogue systems and other fields. However, the factors influencing the sustained use of ChatGPT by university students have not been thoroughly explored. Therefore, this study aimed to delve into the willingness of university students to continue using ChatGPT and identify its influencing and related factors. For this purpose, this study employed quantitative correlational analysis by randomly selecting 400 students for a survey. The data was analyzed using SPSS and AMOS software. Based on the analysis, it can be concluded that perceived usefulness, perceived ease of use, social impact, convenience, and perceived interest had an impact on the willingness of university students to use ChatGPT. Based on this, corresponding strategies and research shortcomings were also presented in this study.